Thermosensitive block copolymer [(PNIPAM)-b-(Glycine)] thin film as protective layer for drug loaded mesoporous silica nanoparticles. (24th October 2017) - Amgoth, Chander; Joshi, Suman
Abstract: Synthesis and characterization of [(PNIPAM)-b-(Gly)] and mesoporous silica nanoparticles (MP-SiO2 NPs) were carried out separately and used to develop [(PNIPAM)-b-(Gly)]-(MP-SiO2 NPs). The synthesized MP-SiO2 NPs were meso porous in nature. The size of SiO2 NPs is in the range of ~180–250 nm (in diameter) with an average pore size of 2.8 nm within the particles. Interestingly, these mesoporous SiO2 NPs were loaded with anticancer drug (ITM-imatinib mesylate) fallow by the incubation for 24 h at RT. However, ITM loaded MP-SiO2 NPs were capped or covered with synthesized [(PNIPAM)-b-(Gly)] thin film. Here, thin film acts as protective layer for drug loaded MP-SiO2 NPs, with that leakage of drug molecules throughout its transport pathway can be avoided. Significantly, thermosensitive [(PNIPAM)-b-(Gly)] polymer thin film depletes at body temperature (~37 °C) and drug molecules come out from the pores of SiO2 NPs. However, developed [(PNIPAM)-b-(Gly)]-(MP-SiO2 NPs) is compatible and used for cell inhibition studies. After 24 h treatment, drug ITM released from [(PNIPAM)-b-(Gly)]-(MP-SiO2 NPs) shows significant (>90%) inhibition on leukemia blood cancer (K562) cells.